New Perspectives on the Community Impact of Rural Education Deserts - Paige N. Park (MDPI AG, 2021)
Understanding how the lack of higher education opportunities due to geographic distance affects perceptions of communities and education is essential in creating sustainable education systems in rural areas. More specifically, this research examines how geographic distance and the absence of institutes, sometimes called an education desert, affect perceptions of community and the perceived value of education. We used data from the 2017 Rural Utah Community Study (RUCS) of residents living in twenty-five rural communities, with a sample size of 1286, and found that the proximity to different types of higher education, four- and two-year institutions, can significantly influence community well-being and the perceived value of education.